COVID-19 hospital indoor environments and how it helped patients’ recovery and staff’s work: a case study in South Korea - Park, Sang Hee; Shin, Hye-Kyung; Kim, Kyoung-Woo (Frontiers in Psychology, 2023)
The indoor environment has been recognized as a crucial factor that can influence health and wellbeing of occupants. This is particularly true in hospital settings, where various environmental attributes can significantly affect patients’ recovery and staff members’ productivity. The present study aimed to investigate how occupants in hospitals perceived indoor environment, focusing specifically on COVID-19 hospitals across Republic of Korea. The study recruited two groups of participants: patients (n = 100) who had been hospitalized in COVID-19 hospitals and staff members (n = 103) who worked in COVID-19 hospitals. The data collected from the participants were analyzed using multiple regression models to determine which environmental attributes significantly affected their perception of the indoor environment. The study revealed that satisfaction with indoor acoustic environment and odor were significant predictors for how patients perceived the indoor environment as helpful for their recovery from COVID-19. On the other hand, odor was also the significant factor affecting staff members’ perceived helpfulness for work. The results suggested that different environmental attributes can have a significant impact on the perception of the indoor environment, depending on the characteristics of occupancy. The study’s findings provided insights into the certain environmental factors that COVID-19 hospitals can prioritize. These insights can help policymakers and hospital administrators to develop strategies to create hospital environments that meet the needs of both groups. The study also suggested that further research is needed to investigate additional factors affecting occupants’ perception of the indoor environment in hospital settings.